On a criterion of Yakubovich type for the absolute stability of nonautonomous control processes - R. Fabbri; S. T. Impram; R. Johnson (International Journal of Mathematics and Mathematical Sciences)
We generalize a criterion of Yakubovich for the absolute stability of control processes with periodic coefficients to the case when the coefficients are bounded and uniformly continuous functions.